Description, history and origins of content analysis analysis in online journalism - M. Nurutdinova; D. Rizayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article explores the unique content analysis in the analysis of journalistic content. The history, development factors and uniqueness of media metrics analysis are revealed. The practice of content learning is also covered in case studies.